Characterization of Lactation Patterns and Milk Yield in a Multibreed Dairy Cattle Population in the Central Thailand - Ameena Seangjun; Skorn Koonawootrittriron; Mauricio A. Elzo (Agriculture and Natural Resources, 2009)
Patterns for five 5 lactation traits: initial yield (IY), peak yield (PY), days to peak (DTP), persistency (PST) and 305-d milk yield (MY) were studied in a multibreed population in Central Thailand using first-lactation, monthly test-day records collected on 108 farms from 1998 to 2006. Breed groups were BG1 (purebred H), BG2 (0.9687 ≤ H < 1.00), BG3 (0.9375 ≤ H < 0.9687), BG4 (0.875 ≤ H < 0.9375) and BG5 (0.50 ≤ H < 0.875). The model for each trait included the fixed effects of herd-yearseason, calving age and breed group. Random effects were cow and residual. Covariance components were estimated using an average information restricted maximum likelihood procedure, and were subsequently used to calculate the heritabilities and genetic correlations. Least square means ranged from 14.16 ± 0.71 kg (BG5) to 16.04 ± 0.66 kg (BG4) for IY, 18.23 ± 0.55 kg (BG5) to 19.84 ± 0.51 kg (BG4) for PY, 36.51 ± 3.78 d (BG4) to 52.04 ± 9.74 d (BG1) for DTP, 6.45 ±0.24 (BG1) to 6.71 ± 0.11 (BG3) for PST, and 4,083.74 ± 103.50 kg (BG5) to 4,317.15 ± 111.56 kg (BG3) for MY. Breed group differences were non-significant. Heritability estimates were 0.23 ± 0.18 for IY, 0.20 ± 0.18 for PY, 0.52 ± 0.28 for DTP, 0.21 ± 0.19 for PST, and 0.43 ± 0.24 for MY. Genetic correlations between MY and IY, PY, DTP and PST were 0.40 ± 0.45, 0.62 ± 0.30, 0.36 ± 0.33, and 0.56 ± 0.39, respectively. These results suggested that PY and PST could be improved resulting in higher MY under the environmental conditions of Central Thailand.